The Impact of COVID-19 on the Education Routines of Students of Determination (SOD) and their Family Members - ALZAABI, ASMA KHALAF (2021)
Covid-19 has impacted virtually every life segment including the normal educational routines. Students, teachers, and parents across the world have faced plenty of emotional and psychological problems because of the ongoing pandemic. Special education or inclusive education is one sector in which the Covid-19 has brought significant problems. Students of Determination (SOD) or students with Special Education Needs (SEN), students with Special Education Needs with Disabilities (SEND), their parents and teachers struggle a lot in conducting the online education smoothly for the aforementioned student community that needs special attention. Teachers have little idea regarding how to teach effectively these student communities online. Parents struggle a lot in making sure that their children with disabilities attend the online classes comfortably. Students with disabilities on the other hand develop plenty of emotional problems because of them being unable to fulfill the challenges of remote learning. The purpose of this study is to identify how educational routines have been affected due to the pandemic and to what extent and mitigation measures are put in place to deal with the new challenges in inclusive education. A mixed-method of research has been used for the collection of data for this study. The study has collected data from SOD, their parents, and teachers working in the private schools in Dubai.